Aktivitas Antibakteri Ekstrak Etanol Daun Alpukat (Persea americana Mill) Terhadap Escherichia coli, Salmonella typhi, dan Pseudomonas aeruginosa - Nasri Nasri; Vera Estefania Kaban; Hariyadi Dharmawan Syahputra; Denny Satria (Program Studi S1 Farmasi, STIKES Senior, Medan, 2022)
Infectious disease is a serious health problem in the world of health. Escherichia coli causes diarrhea, Salmonella typhi causes typhoid fever, and Pseudomonas aeruginosa causes nosocomial infections which are Gram-negative pathogenic bacteria. Treatment with antibiotics is the therapy that is currently used, but other efforts in the use of herbal medicines are also being carried out in various studies. The purpose of this study was to analyze the antibacterial activity of the ethanolic extract of avocado leaves (Persea americana Mill.) against Escherichia coli, Salmonella typhi, and Pseudomonas aeruginosa. The method used is agar diffusion (Kirby-Bauer) with variations in the concentration of the test solution. The results showed that at a concentration of 500 mg/mL the three bacteria had an inhibition zone diameter of Escherichia coli with a value of 12.37±0.15 mm, Salmonella typhi with a value of 11.60±0.20 mm and Pseudomonas aeruginosa with a value of 10.87±0.15 mm. The ethanol extract of avocado leaves (Persea americana Mill.) showed antibacterial activity against three Gram-negative pathogenic bacteria.